2018
DOI: 10.1097/md.0000000000011062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various Danshen injections on patients with coronary heart disease after percutaneous coronary intervention

Abstract: Background:Patients with coronary heart disease (CHD) who undergo percutaneous coronary intervention (PCI) have a certain risk of vascular complications, including coronary restenosis and thrombosis. Many recent randomized controlled trials have reported that Danshen injection (DSI) combined with conventional Western medicine can significantly reduce the occurrence of major cardiovascular adverse events in patients with CHD after PCI. However, there are many types of DSIs, and no study has yet compared each ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Coronary atherosclerotic heart disease, also known as CHD, is the most common type of CVD and one of the deadly diseases among humans (Gao et al, 2017; Liu et al, 2018). The mortality rate of CHD is the highest among all CVDs, accounting for about 40% of all CVD-related deaths (Rezaei-Hachesu et al, 2017; Zhu et al, 2018). Numerous studies have shown that diabetes, hypertension, dyslipidemias, abdominal obesity, unhealthy diet, smoking, and psychosocial stress are major risk factors for CHD (Chow et al, 2007; Gupta et al, 2016; Ajith and Jayakumar, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Coronary atherosclerotic heart disease, also known as CHD, is the most common type of CVD and one of the deadly diseases among humans (Gao et al, 2017; Liu et al, 2018). The mortality rate of CHD is the highest among all CVDs, accounting for about 40% of all CVD-related deaths (Rezaei-Hachesu et al, 2017; Zhu et al, 2018). Numerous studies have shown that diabetes, hypertension, dyslipidemias, abdominal obesity, unhealthy diet, smoking, and psychosocial stress are major risk factors for CHD (Chow et al, 2007; Gupta et al, 2016; Ajith and Jayakumar, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, 25.3% of patients with coronary heart disease still have major adverse cardiovascular and cerebrovascular events within 1 year after PCI, such as myocardial infarction, stroke, and sudden death. With the deepening of coronary artery complexity, the incidence of major adverse cardiovascular and cerebrovascular events is also increasing [8,18,19]. Terefore, the analysis of relevant factors refecting the complexity of coronary artery is helpful to formulate reasonable intervention measures, which has very important clinical guiding signifcance.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 , 27 ] This kind of damage causes the body to repair, while excessive repair may result in vascular restenosis. [ 28 ] PCI treatment may do direct harm to the arterial wall, which may give rise to inflammatory reaction, thrombosis and intimal hyperplasia. [ 29 , 30 ] These changes in vascular wall eventually bring neointimal formation and vascular remodeling, thus leading to restenosis after PCI.…”
Section: Discussionmentioning
confidence: 99%